Dietary flavonols and risk of Alzheimer dementia. (21st April 2020) - Holland, Thomas M.; Agarwal, Puja; Wang, Yamin; Leurgans, Sue E.; Bennett, David A.; Booth, Sarah L.; Morris, Martha Clare
Abstract : Objective: To determine whether dietary intake of flavonols is associated with Alzheimer dementia. Methods: The study was conducted among 921 participants of the Rush Memory and Aging Project (MAP), an ongoing community-based, prospective cohort. Participants completed annual neurologic evaluations and dietary assessments using a validated food frequency questionnaire. Results: Among 921 MAP participants who initially had no dementia in the analyzed sample, 220 developed Alzheimer dementia. The mean age of the sample was 81.2 years (SD 7.2), with the majority (n = 691, 75%) being female. Participants with the highest intake of total flavonols had higher levels of education and more participation in physical and cognitive activities. In Cox proportional hazards models, dietary intakes of flavonols were inversely associated with incident Alzheimer dementia in models adjusted for age, sex, education, APOE [Latin Small Letter Open E]4, and participation in cognitive and physical activities. Hazard ratios (HRs) for the fifth vs first quintiles of intake were as follows: for total flavonol, 0.52 (95% confidence interval [CI], 0.33–0.84); for kaempferol, 0.49 (95% CI, 0.31–0.77); for myricetin, 0.62 (95% CI, 0.4–0.97); and for isorhamnetin, 0.62 (95% CI, 0.39–0.98). Quercetin was not associated with Alzheimer dementia (HR, 0.69; 95% CI, 0.43–1.09). Conclusion: Higher dietary intakes of flavonols may be associated with reduced risk of developing Alzheimer dementia.